Supervisory control of a variable speed wind turbine with doubly fed induction generator - C. Viveiros; R. Melício; J.M. Igreja; V.M.F. Mendes (Energy Reports, 2015)
This paper is on an onshore variable speed wind turbine with doubly fed induction generator and under supervisory control. The control architecture is equipped with an event-based supervisor for the supervision level and fuzzy proportional integral or discrete adaptive linear quadratic as proposed controllers for the execution level. The supervisory control assesses the operational state of the variable speed wind turbine and sends the state to the execution level. Controllers operation are in the full load region to extract energy at full power from the wind while ensuring safety conditions required to inject the energy into the electric grid. A comparison between the simulations of the proposed controllers with the inclusion of the supervisory control on the variable speed wind turbine benchmark model is presented to assess advantages of these controls.
Keywords: 330; Fuzzy PI; LQ; Supervisory control; Wind turbine